2015
DOI: 10.1186/s13046-015-0133-x
|View full text |Cite
|
Sign up to set email alerts
|

Icaritin induces lytic cytotoxicity in extranodal NK/T-cell lymphoma

Abstract: BackgroundExtranodal NK/T-cell lymphoma (ENKL) is an aggressive hematological malignancy associated with Epstein–Barr virus (EBV) infection. It is often resistant to conventional chemotherapy and has a poor prognosis. Icaritin, a compound derived from Chinese herbal medicine, Herba Epimedii, has been reported to exert antitumor effects on a variety of cancer cell lines. In the present study, we investigated the cytotoxic effects of Icaritin on the two EBV-positive ENKL cell lines SNK-10 and SNT-8, along with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 46 publications
(50 reference statements)
0
23
0
Order By: Relevance
“…It has been demonstrated that etoposide causes EBV reactivation in Akata cells . Icaritin induces the expression of EBV lytic genes by inhibiting the LMP1‐mediated STAT3 and Akt pathways . Rituximab and dexamethasone synergistically induce lytic EBV infection, rendering EBV‐positive lymphoma cells more susceptible to GCV cytotoxicity in vitro and in vivo .…”
Section: Lytic‐induction Therapy For Ebv‐positive Tumorsmentioning
confidence: 99%
“…It has been demonstrated that etoposide causes EBV reactivation in Akata cells . Icaritin induces the expression of EBV lytic genes by inhibiting the LMP1‐mediated STAT3 and Akt pathways . Rituximab and dexamethasone synergistically induce lytic EBV infection, rendering EBV‐positive lymphoma cells more susceptible to GCV cytotoxicity in vitro and in vivo .…”
Section: Lytic‐induction Therapy For Ebv‐positive Tumorsmentioning
confidence: 99%
“…Icaritin is a prenylflavonoid derivative from a traditional Chinese herb, Epimedium Genus. Recently, accumulating studies have demonstrated an anti-tumor effect of icaritin in various cancers, including solid tumors and hematological cancers, such as lung cancer (Zheng et al 2014), hepatocel-lular carcinoma (Sun et al 2015;Hu et al 2016;Lu et al 2017), breast cancer (Guo et al 2011;Tiong et al 2012), esophageal cancer (Han et al 2018), glioblastoma Liu et al 2018), leukemia and lymphoma (Zhu et al 2011;Li et al 2013;Li et al 2014;Wu et al 2015;Zhu et al 2015;Yang et al 2019). Icaritin exerts its anti-tumor effects in various cancers mainly by inhibiting cell proliferation, inducing cell differentiation and apoptosis, suppressing cell migration and invasion (Zheng et al 2014;Xu et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Knockdown of STAT3 sensitized BL cells to lytic inducers for reactivation of lytic cycle, while STAT3 inhibition by small molecules, AG490, WP1066, or stattic was found to reactivate lytic cycle of EBV and enhance induction of lytic cycle in EBV-positive BL cells and LCLs by NaB or Aza [ 101 ]. Furthermore, icaritin inhibited STAT3 and AKT pathways by downregulating LMP1 expression, which consequently induced EBV lytic gene expression in ENKL cell lines [ 102 ]. In contrast, berberine was found to repress the level of EBNA1 by inhibiting EBNA1 promoter Qp.…”
Section: Potential Drugs and Strategies In The Future Development mentioning
confidence: 99%